2020
DOI: 10.3892/ol.2020.11476
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of FHL1 protein in glioma inhibits tumor growth through PI3K/AKT signaling

Abstract: Human four-and-a-half LIM domains protein 1 (FHL1) is a member of the FHL protein family, which serves an important role in multiple cellular events by interacting with transcription factors using its cysteine-rich zinc finger motifs. A previous study indicated that FHL1 was downregulated in several types of human cancer and served a role as a tumor suppressive gene. The overexpression of FHL1 inhibited tumor cell proliferation. However, to the best of our knowledge, there is no evidence to confirm whether FHL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…When we prepared our manuscript, a new report showed that downregulation of FHL1 inhibits glioma cell growth in a PI3K/AKT pathway‐dependent manner [27]. These results are not in line with our findings.…”
Section: Discussioncontrasting
confidence: 82%
“…When we prepared our manuscript, a new report showed that downregulation of FHL1 inhibits glioma cell growth in a PI3K/AKT pathway‐dependent manner [27]. These results are not in line with our findings.…”
Section: Discussioncontrasting
confidence: 82%
“…FHL1 interacts with transcription factors and signaling proteins, thus modulating gene transcription and signaling pathways (29, 33). FHL1 suppresses tumor growth through several mechanisms, including interaction with tumor-regulating estrogen receptors and SMAD family proteins, and reduction of PI3K/AKT signaling (29,34,35). The FHL1 3’-UTR was significantly lengthened (P=0.029), and FHL1 gene expression was significantly enriched, in CPSF3 knockdown cells, as compared with shNTC controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, this list included multiple downregulated oncogenes, including SMAD Family Member 6 (SMAD6) and Mitogen-Activated Protein Kinase Kinase 6 We next sought to determine if any of the APA-regulated oncogenes or tumor suppressors were directly responsible for CPSF3 knockdown-mediated attenuation of cell proliferation. We focused on FHL1, as it has been reported to possess tumor suppressor activity in non-PDAC cancers (29)(30)(31)(32), but has no known roles in PDAC biology. FHL1 interacts with transcription factors and signaling proteins, thus modulating gene transcription and signaling pathways (29,33).…”
Section: Cpsf3 Knockdown Dysregulates Global Gene Expression In Pdac ...mentioning
confidence: 99%
“…For TGFb/ Smad-independent way, PI3K/Akt, MAPK, Nuclear Factor Kappa-B (NF-kB), Hedgehog, and Wnt/b-catenin pathways were upstream regulators of EMT-TFs (38)(39)(40)(41). Some studies pointed out that FHLs can increase the activation and transcription of Akt to promote tumor growth and progression in glioma, breast cancer, and ovarian cancer (30,42,43). Other published papers showed that FHLs interfere with the MAPK/ERK pathway, resulting in radiotherapy resistance in pancreatic cancer (44).…”
Section: Discussionmentioning
confidence: 99%